Acquisition of human plasminogen facilitates complement evasion by the malaria parasite Plasmodium falciparum. Issue 2 (15th November 2020) - Reiss, Timo; Theis, Hannah I.; Gonzalez‐Delgado, Andres; Vega‐Rodriguez, Joel; Zipfel, Peter F.; Skerka, Christine; Pradel, Gabriele
Abstract : We show that the intraerythrocytic stages of the malaria parasite Plasmodium falciparum bind plasminogen and mediate its conversion into plasmin to inactivate parasite‐bound C3b. This complement evasion mechanism counteracts terminal complex formation and hence promotes parasite survival in human blood.